Rushton bodies - a pathological enigma - Pereira, Treville; Shetty, Subraj (Brazilian Dental Science, 2015)
The most common inflammatory odontogenic cyst is the radicular cyst. It forms as a result of pulp necrosis due to the presence of carious teeth. Rushton bodies may be seen as irregular structures on the surface epithelium of odontogenic cysts. We present a rare case of a radicular cyst showing rushton bodies in a 47-year-old male patient.